Trust in Science, Perceived Media Exaggeration About COVID-19, and Social Distancing Behavior - Neureiter, Ariadne; Stubenvoll, Marlis; Kaskeleviciute, Ruta; Matthes, Jörg (Frontiers in Public Health, 2021)
For many individuals, the media function as a primary source of information about preventative measures to combat COVID-19. However, a considerable number of citizens believe that the media coverage about pandemics is exaggerated. Although the perception of media exaggeration may be highly consequential for individual health behaviors, we lack research on the drivers and consequences of this perception. In a two-wave panel study, we examined associations between trust in science, perceptions of media exaggeration about COVID-19, and social distancing behavior during the lockdown in Austria (NT2 = 416). Results showed that trust in science at T1 led to less perceptions of media exaggeration about COVID-19 at T2. Furthermore, consistent with the theory of psychological reactance, perceptions of media exaggeration about COVID-19 at T1 caused less social distancing behavior at T2. Thus, findings suggest that trust in science may positively affect individuals' social distancing behavior by decreasing perceived media exaggeration about COVID-19 over time. Implications for research on media effects in times of COVID-19 and conclusions for journalists are discussed.